PREPARATION AND CHARACTERIZATION OF ATORVASTATIN-LOADED POLYVINYLPIRROLIDONE-BASED ELECTROSPUN MICROFIBROUS MATS - RÉDAI, Emőke; RÁDULY, Izabella; SZABÓ, Zoltán-István; CIURBA, Adriana; TODORAN, Nicoleta; ANTONOAEA, Paula; VLAD, Robert-Alexandru; PÉTERFI, Orsolya; SIPOS, Emese (Studia Universitatis Babeș-Bolyai Chemia, 2021)
The aim of this experimental work was the enhancement of water solubility of the lipid lowering drug, atorvastatin, by embedding it in polymer based micro-sized fibers, prepared by electrospinning. Characterization of the fibrous mats included morphological investigations, determination of drug content, disintegration time, small volume dissolution- and DSC studies. The electrospinning process was continuous without droplet formation. The obtained fibers were homogenous, continuous filaments with smooth surfaces. Average fiber diameters were slightly above 1 µm, while disintegration of fiber mats upon contact with water was almost instantaneous (three to ten seconds). Dissolution of the lipid lowering drug was almost complete, when using a solution feed rate of 1 mL/h.